335 RENAL HEMODYNAMIC RESPONSES TO CYCLOOXYGENASE-2 INHIBITION IN RATS DURING ACUTE AND CHRONIC ANGIOTENSIN-CONVERTING ENZYME INHIBITION. (1st January 2005) - Green, T.; Rodriguez, J.; Navar, L. G.
Abstract : Chronic ACE inhibition has been demonstrated to increase kidney COX2 expression. Thus we conducted studies in rats during acute and chronic ACE inhibition to evaluate the hemodynamic consequences of upregulated COX2 expression and to determine whether the effects of COX2 inhibition are independent of renin release and angiotensin II unopposed vasoconstriction. Anesthetized Sprague-Dawley rats were given captopril chronically (100 mg/kg/day, orally) and/or acutely (5 mg/kg, intraarterial) followed by acute COX2 inhibition with nimesulide (3 mg/kg). Nimesulide administration during chronic ACE inhibition caused significant reductions in GFR (0.83 ± 0.06 to 0.59 ± 0.06 mL/min/g kidney weight), RPF (4.21 ± 0.15 vs. 3.63 ± 0.24 mL/min/g kidney weight), urine flow (11 ± 2 vs. 6.5 ± 2 μL/min) and medullary blood flow (115 ± 13 to 87 ± 12 mV) without significant alteration in mean arterial pressure (92 ± 3.3 mm Hg), cortical blood flow (376 ± 46 mV) and sodium excretion (0.57 ± 23 μEq/min). During acute ACE inhibition, nimesulide also caused significant changes in GFR (1.22 ± 0.1 to 0.85 ± 0.07 mL/min/g kidney weight), RPF (4.48 ± 0.26 to 3.83 ± 0.22 mL/min/g kidney weight), urine flow (18 ± 2 to 11 ± 1 μL/min), medullary blood flow (132 ± 13 vs. 112 ± 17 mV) and sodium excretion without significantly altering MABP (96 mm Hg), cortical blood flow (500 ± 58 mV) or sodium excretion (0.93 ± 0.11 μEq/min). The percentage changes in RBF and GFR were not significantly different between the acutely and chronically ACE inhibited rats. However, unlike normal rats, acute ACE inhibition increased renal hemodynamic sensitivity to nimesulide. In conclusion, these data demonstrate that both acute and chronic ACE inhibition results in increased renal hemodynamic sensitivity to COX2 inhibition. Although chronic ACE inhibition led to upregulation of TAL COX2 expression, this did not result in greater sensitivity to COX2 inhibition. Since we observed nimesulide effects on hemodynamics during ACE inhibition, we further conclude that the hemodynamic effects of COX2 are not fully dependent on unopposed angiotensin II vasoconstriction.